Numerical Investigation of Pelton Turbine with Experimental Validation - Bijukchhe, Pawan Lal; Chitrakar, Sailesh; Chaulagain, Nabin Raj; Timilsina, Prabin (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Computational Fluid Dynamics (CFD) has been established as a prominent tool for the effective analysis and optimization of hydro-turbines. Various CFD codes, both commercial type and open-source type, are being used in the industry for flow simulation and optimization. For impulse turbines like Pelton, the numerical simulation requires solving of various complex phenomena like multi-phase fluid interaction, multi-reference frame study, jet-bucket interaction and free-surface transient flows. A number of simplifications has to be made in terms of the geometry and flow physics for solving the flow problem in reasonable time and less computational cost. The aim of this research is to use OpenFOAM to develop a numerical model for flow analysis of Pelton turbine with an existing bucket geometry, and compare the results with experimental data. A numerical model consisting of three buckets was studied, out of which the torque produced in the middle bucket during a transient flow was observed and results were compared with the experimental data from project carried out in Norwegian University of Science and Technology. The jet of water hitting the bucket is modelled as a cylinder with a constant diameter corresponding to a defined opening of the spear valve. The snappyHexMesh utility of OpenFOAM was used for meshing the geometry and interFoam solver with laminar turbulence model was used to simulate the flow over buckets. The results obtained have shown a good concurrence with the actual values from the experiment.